Strengthening the competitiveness of SMEs by using funds from EU funds on the example of Zadar County - Marasović, Marina (Oeconomica Jadertina, 2021)
Micro, small and medium-sized enterprises (SMEs for short) represent 99% of all enterprises in the EU. They are considered to be the drivers of the European economy. The definition of SMEs is important for access to finance and EU support programs targeted at these companies. In the Republic of Croatia, SMEs make up about 90% of the total number of all companies in which about 48% of persons are employed. The lifespan of SMEs is generally shorter news, and many scientists believe the reason is actually market entry. "With Croatia's accession to the EU, financial resources from European funds have become easier to use. The EU finances projects with funds from centralized and decentralized programs" (Kociper et al. 2014, 90). Centralized programs are managed directly in Brussels and are used to fund EU-wide priorities, while decentralized programs are individual Member State programs, which fund priorities of importance to the Member State in line with strategic objectives at EU level.
Keywords: Micro, small and medium enterprises; EU funds; operational programs; Zadar County